ANALISIS PSIKOLOGI SASTRA DAN NILAI MORAL DARI NOVEL CINTA SUCI ZAHRANA KARYA HABIBURAHMAN EL SHIRAZY - Nayla Azkani; Rahmat Kartolo (Jurnal Inovasi Penelitian, 2023)
This study aims to determine the Literary Psychology and Moral Values of the Novel Cinta Suci Zahra by Habiburahman El Shirazy. This research is a descriptive qualitative using a structuralism approach. The activities carried out in this study were reading, observing, interpreting and analyzing the novel Cinta Suci Zahrana. The data sources in this study are: (1) text, the novel Cinta Suci Zahrana; (2) field notes consisting of two parts, namely the description section and the reflection section. The data collection techniques used are the documentation method and the review method. From the analysis carried out, the literary psychology contained in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy is found in chapter "Hope" page 43, in chapter "Hunting for Tranquility" pages 223-224, in chapter "Suffering is Complete" pages 247-248 and 254, then in chapter "Who Sows He Reaps" page 270. While the moral values in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy consist of three moral aspects, namely moral aspects related to oneself, moral aspects related to other human beings, and moral aspects related to His God. From the analysis conducted, it can be said that the novel Cinta Suci Zahrana by Habiburrahman El Shirazy contains literary psychology and moral values